2011
DOI: 10.1094/cchem-11-10-0163
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Oat Varieties and Their Potential for Breadmaking

Abstract: The breadmaking potential of six oat varieties was compared with and related to their physicochemical properties. The most significant differences in the bread characteristics were found in the crumb structure. The varieties Buggy, Energie, and Zorro resulted in good bread quality with an even gas‐cell distribution characterized by a high number of relatively small pores. In contrast, Typhon, Ivory, and Nord 08/311 each had a large hole in the center of the crumb and accordingly poor quality. Breads differed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…However, none of the samples can be highlighted as significantly different one. The viscous properties of the cultivars were similar to those reported in literature (Choi et al., 2012; Hüttner et al., 2011).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…However, none of the samples can be highlighted as significantly different one. The viscous properties of the cultivars were similar to those reported in literature (Choi et al., 2012; Hüttner et al., 2011).…”
Section: Resultssupporting
confidence: 86%
“…Also, oat breeding is mainly directed by agronomic properties such as seed size, yield, and lodging resistance or by nutritional attributes such as protein, lipid, or β‐glucan content (Lapveteläinen et al., 2001; Valentine et al, 2011). Examinations of oat cultivars showed that there can be great differences in their composition (Boeck et al., 2018) and in the techno‐functional behaviors of their flours such as hydration, batter rheology, pasting properties, and also baking performance (Choi et al., 2012; Hüttner et al., 2011; Sunilkumar et al., 2017; Zhang et al, 2019). This indicates that more detailed quality requirements similarly to that of wheats might be needed to determine the end‐use quality of oats and to investigate their applicability in the different food sectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, most of the oat cultivar samples were baked with good or excellent quality by the dough yield optimisation. Previously, specific volumes of 1.14-1.66 mL/g have been reported for whole oat breads [16,17], while in our study, specific volumes were greater (1.45-1.93 mL/g). However, a good loaf bread shape using wheat baking quality criteria was challenging to obtain with our gluten-free baking method.…”
Section: Discussioncontrasting
confidence: 65%
“…The objective of this study was to assess the baking quality variation of twenty whole grain oat cultivar samples, and to identify the factors that caused the variation. In previously published whole oat baking studies, oat cultivars and processing steps were not controlled [16], or the oat was not properly kilned [17]. Kiln treatment is included in oat processing to increase the shelf-life of oat and to prevent enzymatic rancidity, since oat contains high levels of fat and lipolytic enzymes [18].…”
Section: Discussionmentioning
confidence: 99%